2017
DOI: 10.1017/s1751731117001173
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress effects on Holstein dairy cows’ rumination

Abstract: The objective of this study was to investigate the relationship between temperature-humidity index (THI) and rumination time (RT) in order to possibly exploit it as a useful tool for animal welfare improvement. During summer 2015 (1 June to 31 August), data from an Italian Holstein dairy farm located in the North of Italy were collected along with environmental data (i.e. ambient temperature and relative humidity) recorded with a weather station installed inside the barn. Rumination data were collected through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 25 publications
6
41
2
1
Order By: Relevance
“…The effect of the season has a significant effect on the feed intake and daily milk production parameters evaluated by us. Negative changes in chewing parameters are attributed by other authors to the heat stress that dairy cows suffer during the summer months (VI-VIII), when on average dairy cows chewed the shortest time in our work (Dado and Allen, 1994;Acatinai et al, 2010;Bernabucci et al, 2010;Soriani et al, 2013, Moretti et al, 2017. In contrast, in the winter (XII-II), dairy cows chewed in our work for a long time, which is agreed with other studies.…”
Section: -Ii XII -Ii Xii -Ii Xii -Ii Iii -supporting
confidence: 92%
See 1 more Smart Citation
“…The effect of the season has a significant effect on the feed intake and daily milk production parameters evaluated by us. Negative changes in chewing parameters are attributed by other authors to the heat stress that dairy cows suffer during the summer months (VI-VIII), when on average dairy cows chewed the shortest time in our work (Dado and Allen, 1994;Acatinai et al, 2010;Bernabucci et al, 2010;Soriani et al, 2013, Moretti et al, 2017. In contrast, in the winter (XII-II), dairy cows chewed in our work for a long time, which is agreed with other studies.…”
Section: -Ii XII -Ii Xii -Ii Xii -Ii Iii -supporting
confidence: 92%
“…A slightly higher correlation (r = 0.384) than in our study, but also a positive correlation between chewing time and daily milk, is described in the study by Antanatias et al (2018). Stone et al (2017) reported a moderate correlation between milk yield and chewing time at (r = 0.22) (Antanaitis et al, 2018;Moretti et al, 2017), with our calculated correlations between good chewing and performance is slightly lower (r = 0.166).…”
Section: Discussionmentioning
confidence: 44%
“…Rumination activity is influenced mainly by diet characteristics (Erina et al, 2013;Welch & Smith, 1970) therefore the decrease in rumination activity after the change of system may be due to changes in the composition of the diet. But also, rumination activity is negatively affected by different stressors, such as high stocking density, heat stress, and acute stress (Grant & Albright, 2001;Herskin, Munksgaard, & Ladewig, 2004;Kadzere, Murphy, Silanikove, & Maltz, 2002;Moallem, Altmark, Lehrer, & Arieli, 2010;Moretti, Biffani, Chessa, & Bozzi, 2017). In addition, more stressed cows (with greater serum cortisol concentration) spent less time ruminating (Bristow & Holmes, 2007;Lindström, Redbo, & Uvnäs-Moberg, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress is an important threat to cattle breeding, especially in the Mediterranean basin [29], where the combination of high temperatures and high humidity can result in harsh conditions for dairy cows. This situation can be exacerbated by air velocity and the intensity of solar radiation, particularly in unshaded areas of a barn [25].…”
Section: Introductionmentioning
confidence: 99%